The needs ABC therapeutic model for couples and families : a guide for practitioners - Caplan, Tom (New York : Routledge, 2010)
'The Needs ABC Therapeutic Model for Couples and Families: A Guide for Practitioners shows readers how to successfully tailor a therapeutic approach to meet the needs of couples and families. It has been preceded by Needs ABC (Acquisition and Behavior Change), a model for group work and other psychotherapies published in the UK by Whiting and Birch. Beginning clinicians will come away from this book with concrete, practical skills and expanded theoretical base for their practice, and they'll be able to apply their new knowledge directly and in ways that will help them create long-lasting change in clients who present with difficult behaviors. The book explains the concepts and theories behind the Needs ABC approach and provides tangible methods with which to perform as a Needs ABC therapist or integrate aspects of the Needs ABC approach into the reader's own therapeutic techniques. Practitioners will find that the Needs ABC model complements cognitive-behavioral, integrative, and other therapeutic models, as well as general guides to couples and family therapy'--Provided by publisher
Includes bibliographical references and index
Keywords: Couples Therapy -- Methods; Family Therapy -- methods